Multiple interactions between fishbone instabilities and internal transport barriers in EAST plasmas. (1st January 2023) - Ge, Wanling; Wang, Zheng-Xiong; Wang, Feng; Liu, Zixi; Xu, Liqing
Abstract: Fishbone instabilities and internal transport barriers (ITBs) are frequently and sequentially observed in tokamak plasmas. Recently, the relationship between fishbone instabilities and ITBs was numerically studied, mainly on the basis of experimental results (Liu et al 2020 Nucl. Fusion 60 122001). It was identified that a radial electric field can be generated by the fishbone itself, which may act as a trigger for ITB formation. To gain a deeper understanding of this subject, in this work we further demonstrate the multiple interactions between fishbone instability and ITBs in Experimental Advanced Superconducting Tokamak (EAST) experiments (discharge #56933) using the hybrid kinetic-MHD code M3D-K. In multiple- n simulations, it is found that a zonal electric field can be induced in the nonlinear fishbone stage, leading to a relatively large E × B zonal flow that is sufficient to suppress the dominant microinstability before ITB formation; this should account for ITB triggering. After the ITB is triggered, the equilibrium pressure gradient increases and fast ions from the neutral beam injection accumulate in the ITB region. Linear simulations are performed to analyze the effect of ITB formation on fishbone instability. It is shown that due to the change of the pressure gradient during ITB expansion, the change in the bootstrap current density profile modifies the q -profile and then stabilizes the fishbone mode. Additionally, the accumulation of the fast ions leads to a broadening of fast ion distribution around the ITB region, which also has a stabilizing effect on the fishbone mode.